Dermal Lymphatic Invasion, Survival, and Time to Recurrence or Progression in Inflammatory Breast Cancer. (September 2021) - Hirko, Kelly A.; Regan, Meredith M.; Remolano, Marie C.; Schlossman, Julia; Harrison, Beth; Yeh, Eren; Jacene, Heather; Nakhlis, Faina; Block, Caroline; Rosenbluth, Jennifer M.; Garrido-Castro, Ana C.; Overmoyer, Beth A.
Abstract : Objectives: Dermal lymphatic invasion (DLI) with tumor emboli is a common pathologic characteristic of inflammatory breast cancer (IBC), although its presence is not required for diagnosis. We examined whether documented DLI on skin biopsy was associated with survival and time to recurrence or progression in IBC. Materials and Methods: A total of 340 women enrolled in the IBC Registry at Dana-Farber Cancer Institute between 1997 and 2019 were included in this study. Kaplan-Meier curves and multivariable Cox proportional hazards models were used to estimate hazard ratios and 95% confidence intervals for associations of DLI and overall survival, time to locoregional recurrence/progression, and distant metastasis by stage at presentation. Results: DLI was detected in 215 (63.2%) of IBC cases overall. At disease presentation, IBC with DLI had a higher prevalence of de novo metastases (37.7% vs. 26.4%), breast skin ulceration (6.1% vs. 2.4%), and lymphovascular invasion within the breast parenchyma (52.9% vs. 25.5%) and a lower prevalence of palpable breast mass (48.2% vs. 70.6%) than IBC without DLI. Over a median follow-up of 2.0 years, 147 deaths occurred. DLI was not associated with survival or recurrence in multivariable models (all P ≥0.10). For example, among women with stage III disease, hazard ratios (95% confidence intervals) for DLI presence was 1.29 (0.77-2.15) for overall survival, 1.29 (0.56-3.00) for locoregional recurrence, and 1.71 (0.97-3.02) for distant metastasis. Conclusion: Although the extent of tumor emboli in dermal lymphatics may be associated with biological features of IBC, DLI was not an independent prognostic marker of clinical outcomes in this study. Abstract : Supplemental Digital Content is available in the text.